An An Association Between Administrative Factors and Mortality in ST-Segment Elevation Myocardial Infarction Patients of Hospitals in Thailand - Vichairuangthum, Kitigon (European Journal of Applied Sciences, 2022)
This descriptive study aimed to study an association between the level of readiness of administrative factors and the mortality rate of patients with acute ischemic heart disease of hospitals in Thailand, Target population were 1,180 hospitals that serving heart disease in Thailand. Data were collected by using a questionnaire. A total of 1,022 response data were obtained. Administrative factors were analyzed using descriptive statistics and correlation was analyzed by multiple regression analysis (MRA) methods. The results showed that the administrative factors which consisted of personnel, finance, supporting, and management factors had overall average readiness at a high level (x̄ = 3.34, S.D. = 0.27). Except budget sufficiency was at a low level (x̄ = 2.43, S.D. = 0.43). All factors were significantly related to the mortality rate, as follows: management factor (Adjusted R2 = 0.433), personnel factor (Adjusted R2 = 0.231), supporting factor (Adjusted R2 = 0.092) and financial factor (Adjusted R2 = 0.035). Therefore, Thai Ministry of Public Health should provide adequate support for administrative factors especially in terms of management, personnel, and budget sufficiency.